2020
DOI: 10.3390/antiox9080669
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Polyphenols as Antioxidant and Anti-Inflammatory Compounds in Brain–Liver–Gut Axis

Abstract: Oxidative stress plays an important role in the onset as well as the progression of inflammation. Without proper intervention, acute inflammation could progress to chronic inflammation, resulting in the development of inflammatory diseases. Antioxidants, such as polyphenols, have been known to possess anti-oxidative properties which promote redox homeostasis. This has encouraged research on polyphenols as potential therapeutics for inflammation through anti-oxidative and anti-inflammatory pathways. In this rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 102 publications
(206 reference statements)
1
36
0
1
Order By: Relevance
“…Both PAMPs and DAMPs are recognized by various pattern recognition receptors (PRRs), such as Toll-like receptors (TLRs) [18][19][20]. The activation of PRR induces intracellular signaling cascades, such as kinases and transcription factors [19,21]. The signaling pathways mentioned above can promote the production of a variety of inflammatory mediators (such as cytokines) for inflammation development.…”
Section: The Anti-inflammatory Activity Of Resveratrolmentioning
confidence: 99%
“…Both PAMPs and DAMPs are recognized by various pattern recognition receptors (PRRs), such as Toll-like receptors (TLRs) [18][19][20]. The activation of PRR induces intracellular signaling cascades, such as kinases and transcription factors [19,21]. The signaling pathways mentioned above can promote the production of a variety of inflammatory mediators (such as cytokines) for inflammation development.…”
Section: The Anti-inflammatory Activity Of Resveratrolmentioning
confidence: 99%
“…Because of antioxidant properties and free-radical scavenging activity, they are believed to protect against various diseases, e.g., cancer, stroke and myocardial infarction, cardiovascular diseases, and some immunological and neurological disorders; they are also thought to have a beneficial impact on humans with diabetes and obesity [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Several in vitro and in vivo animal studies have demonstrated the antioxidant and anti-inflammatory effects of polyphenols in the brain–liver–gut axis [ 32 ], and polyphenols have been shown to target different stages of the inflammatory cascade to reduce the severity of inflammation. Polyphenols can also modulate various signal pathways, for example, through interaction with AMP-activated protein kinase (AMPK), CCAAT/enhancer-binding protein α (C/EBPα), peroxisome proliferator-activated receptor γ (PPARγ), and peroxisome proliferator-activated receptor-gamma coactivator 1-alpha (PGC-1α), sirtuin 1, and sterol regulatory element-binding protein-1c (SREBP1c) involved mainly in cellular energy metabolism and adipogenesis, as well as uncoupling proteins 1 and 2 (UCP1 and UCP2), and NF-κB that regulate antioxidant and anti-inflammatory responses [ 28 ].…”
Section: The Structure and Role Of Polyphenolsmentioning
confidence: 99%
“…The gut microbiota composition is highly variable among individuals. Its heterogeneity has an association with both intrinsic factors (genetics, genders, and age) and extrinsic factors (diet, herbs, polyphenols, age, antibiotics, lifestyle, and disease status) [ 72 ]. With aging, the diversity and amount of gut microbiota decrease.…”
Section: Improvement Of the Gut–liver–brain Axis By Chungkookjangmentioning
confidence: 99%